Bilateral testicular torsion in a 36-week neonate. (7th February 2018) - Clarke, Michael J H; Crocker, Samuel; Bartle, David G; Apsey, John
Abstract : A male neonate born after uncomplicated vaginal delivery at 36 weeks' gestation was noted to have large and firm testicles bilaterally on routine examination. A testicular ultrasound scan was subsequently organised that showed detailed appearances consistent with bilateral testicular torsion. This was thought to have taken place antenatally and as such was unfortunately not suitable for intervention. The patient was therefore managed conservatively with the testicles left to involute naturally. He was started on testosterone replacement therapy after follow-up when gonadotrophin levels were found to be raised and testosterone low (suggesting absent testicular function) and will be closely followed up regarding his future development which is normal to this point.